2017
DOI: 10.3390/f8110430
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Soil Properties, Enzyme Activities and Microbial Communities in Heavy Metal Contaminated Bulk and Rhizosphere Soils of Robinia pseudoacacia L. in the Northern Foot of Qinling Mountain

Abstract: Abstract:The toxic effects of heavy metal (HM) contamination on plant metabolism and soil microorganisms have been emphasized recently; however, little is known about the differences in soil physical, chemical, and biological properties between bulk and rhizosphere soils contaminated with HMs in forest ecosystem. The present study was conducted to evaluate the rhizosphere effect on soil properties, enzyme activities and bacterial communities associated with Robinia pseudoacacia L. along a HM contamination grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…The increased urease and phosphatase activities in the rhizosphere-associated soil samples suggest that these soils may have increased mineralization rates of soil organic nitrogen and phosphorus compared to the unvegetated site. Similar to our findings, Yang et al [39] found significantly higher activities of β-glucosidase, urease and phosphatase in the rhizosphere soils of Robinia pseudoacacia compared to those of bulk soil. In addition, our results showed that the ratios of bacterial to fungal PLFAs increased in un-vegetated soil samples compared to those of vegetated soil samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The increased urease and phosphatase activities in the rhizosphere-associated soil samples suggest that these soils may have increased mineralization rates of soil organic nitrogen and phosphorus compared to the unvegetated site. Similar to our findings, Yang et al [39] found significantly higher activities of β-glucosidase, urease and phosphatase in the rhizosphere soils of Robinia pseudoacacia compared to those of bulk soil. In addition, our results showed that the ratios of bacterial to fungal PLFAs increased in un-vegetated soil samples compared to those of vegetated soil samples.…”
Section: Discussionsupporting
confidence: 92%
“…Plant roots support larger populations of microorganism in their rhizosphere compared to non-rooted bulk soil [38, 39] by releasing organic material as root exudates [38], that increased microbial biomasses and their enzyme activities [40]. In the present work, the bacterial and fungal biomasses (PLFA abundance) were significantly higher in the vegetated sites compared to the un-vegetated sites; the superior levels of microbial biomass in the vegetated sites were also associated with greater rates of soil respiration and greater enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DTPA extractable Zn is considered to be the bio-available Zn and having a concern with respect to the toxicity to the environment and plant uptake and utilization 19 . Yang et al 20 studied the soil properties of the different Zn contaminated sites of China and reported that the soil organic matter, available nitrogen and phosphorus were significantly high in rhizosphere soil compare to their bulk soils at Zn contaminated sites reveled the role of associated heavy metal tolerant plant growth promoting rhizospheric bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is easily measured, it could provide a useful tool for environmental monitoring (Rao et al 2014). In addition, understanding the effects of heavy metals on soil enzyme activity may also provide an opportunity for an integrated assessment of soil biology (Yang et al 2017). Increased contents of heavy metals in soil above a certain threshold generally adversely affect the growth, morphology, and metabolism of microorganisms, which leads to a decrease in the functional diversity of soil ecosystems (Hassan et al 2013).…”
Section: Introductionmentioning
confidence: 99%